Exit strategy to ease or eliminate tax responses to the COVID-19 pandemic. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Tax stimuli in the region were designed to pull economies out of the pandemic-induced recession. Using illustrative cases, the brief examines tax stimuli and estimates overall tax losses and losses attributable to tax measures, along with the risks associated with such measures. It provides guidelines on an appropriate strategy between a staggered or simultaneous exit and offers recommendations on specific tax measures for exit processes and the post-exit stage.
Keywords: Taxation -- Economic aspects; Public administration; Electronic book